Case report: A novel 5'-UTR-exon1-intron1 deletion in MLYCD in an IVF child with malonyl coenzyme A decarboxylase deficiency and literature review - Xu, Fang; Wu, Yangyang; Huang, Jiyi; Zhou, Yunguo; Xu, Fei; Duan, Junkai; Li, Hong (Frontiers in Medicine, 2023)
The subject of the study is an 11-month old IVF baby girl with the typical clinical manifestation of malonyl coenzyme A decarboxylase deficiency, including developmental delay, limb weakness, cardiomyopathy, and excessive excretion of malonic acid and methylmalonic acid. Whole genome sequencing (WGS) revealed a novel heterozygous nonsense mutation (c.672delG, p.Trp224Ter) in the MLYCD gene of the proband and her father and a novel heterozygous deletion in 5'-UTR-exon1-intron1 of the MLYCD gene of the proband and her mother. The patient's cardiac function and limb weakness improved considerably after 3 months of a low-fat diet supplemented with L-carnitine. Furthermore, mapping of gene mutations and clinical manifestations was done by case collection.